Advances in the determination of anabolic-androgenic steroids: From standard practices to tailor-designed multidisciplinary approaches - Huml, L.; Tauchen, J.; Rimpelová, S.; Holubová, B.; Lapzík, O.; Jurásek, M. (Sensors, 2022)
Anabolic-androgenic steroids (AASs), a group of compounds frequently misused by athletes and, unfortunately, also by the general population, have lately attracted global attention; thus, significant demands for more precise, facile, and rapid AAS detection have arisen. The standard methods ordinarily used for AAS determination include liquid and gas chromatography coupled with mass spectrometry. However, good knowledge of steroid metabolism, pretreatment of samples (such as derivatization), and well-trained operators of the instruments are required, making this procedure expensive, complicated, and not routinely applicable. In the drive to meet current AAS detection demands, the scientific focus has shifted to developing novel, tailor-made approaches leading to time- and cost-effective, routine, and field-portable methods for AAS determination in various matrices, such as biological fluids, food supplements, meat, water, or other environmental components. Therefore, herein, we present a comprehensive review article covering recent advances in AAS determination, with a strong emphasis on the increasingly important role of chemically designed artificial sensors, biosensors, and antibody- and fluorescence-based methods.